2021
DOI: 10.1080/16549716.2021.1901390
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening routine health data analysis in Ethiopia: the Operational Research and Coaching for Analysts (ORCA) experience

Abstract: Many routine health information systems (RHIS) show persistent gaps between recording and reporting data and their effective use in solving problems. Strengthening RHIS has become a global priority to track and address national health goals. In Ethiopia, the Ministry of Health and Bill & Melinda Gates Foundation introduced the Operational Research and Coaching for Analysts (ORCA) capacity development project, co-designed with the London School of Hygiene & Tropical Medicine, which delivered training, coaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In these, HISs have been used for much longer than in other nations of the world [ 61 ]. Nevertheless, RHISs continue to display a gap between recording, reporting, and the effective use of data; therefore, strengthening RHISs has become a global priority for tracking and addressing national health goals [ 62 ]. The operations of RHISs in low-income countries fall below the globally expected standard due to the production and use of poor quality data, or to not using high-quality data to make informed decisions [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these, HISs have been used for much longer than in other nations of the world [ 61 ]. Nevertheless, RHISs continue to display a gap between recording, reporting, and the effective use of data; therefore, strengthening RHISs has become a global priority for tracking and addressing national health goals [ 62 ]. The operations of RHISs in low-income countries fall below the globally expected standard due to the production and use of poor quality data, or to not using high-quality data to make informed decisions [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…RHIS data from the research and health policy community in Mozambique will help build sustainable long-term capabilities to manage and evaluate health conditions effectively [ 68 ]. In Ethiopia, the Ministry of Health and the Bill & Melinda Gates Foundation (Bill & Melinda Gates Foundation) launched “Operational Research and Coaching for Analysts” (ORCA) as a method for developing data collection and reporting [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another article mentions the role of doctors have in implementing health information systems (HR) in health services by improving the quality of health information systems as an effort to improve health services ( 36 ). Health information technology is indeed not the only effort to complete an information system, but it needs other components such as timely, complete, and accurate data as well as support from organizations such as feedback on reports and so on ( 37 ). This all will certainly affect the quality of information system data ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the nationwide transition from a fragmented electronic health management information system (HMIS) to a unified, web-based District Health Information System 2 (DHIS2), intensive trainings were provided to health workers on HMIS indicator definition, data capturing, and reporting. 9 , 21 The deployment of a standardized electronic data aggregation and reporting system and accompanying capacity-building activities have facilitated observed improvements in reporting completeness. Other studies have also shown that data reporting improves after an electronic, web-based HMIS platform is introduced in-country.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…These findings are consistent with previous studies’ observations of the limited data analysis, interpretation, and problem-solving skills among health workers and how this, in turn, hinders information use at the point of care. 17 , 21 , 28 This implies that capacity-building interventions are needed to improve the analytical skills of health workers and health facility managers. Integrating simple digital data analysis tools and dashboards as part of the CBMP intervention package, along with targeted skill development, would help address this gap.…”
Section: Lessons Learnedmentioning
confidence: 99%